The Influence of Brand Consciousness on Repurchase Intention with Customer Loyalty as a Mediation Variable in Islamic Business Perspective (Study on Generation Z Colorbox Customers in Bandar Lampung) - Mella Rosyana Fitri; Vicky F Sanjaya; Sania Nuraziza (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of Brand Consciousness and Repurchase Intention mediated by Customer Loyalty on Generation Z Colorbox customers in Bandar Lampung in the perspective of Islamic Business. This study focused on 96 respondents from Generation Z in Bandar Lampung. selected through purposive sampling techniques. The research method used is a quantitative method with data collection techniques through questionnaires. Data analysis was conducted using structural equation model approach with SmartPLS 4 application. The findings showed that the existence of positive and significant influence between the relationship of Brand Consciousness to Repurchase Intention, Brand Consciousness to Customer Loyalty, Customer Loyalty to Repurchase Intention, and Customer Loyalty was able to mediate the relationship between Brand Consciousness and Repurchase Intention. In the perspective of Islamic business, all economic activities must be based on Sharia values such as honesty, justice, responsibility, and not harming others.